Development of novel zirconia implant's materials gradated design with improved bioactive surface. (June 2019) - Faria, D.; Pires, J.M.; Boccaccini, A.R.; Carvalho, O.; Silva, F.S.; Mesquita-Guimarães, J.
Abstract: Zirconia implants are becoming a preference choice for different applications such as knee, dental, among others. In order to improve osseointegration, implant's surfaces are usually coated with bioactive materials like hydroxyapatite (HAp) and beta-tricalcium phosphate (β-TCP) that are very similar to the calcium phosphates found in bones. However, due to the implantation process, these coatings can be detached from the zirconia surface, leading to implant premature failure. In this work, a new component materials design aiming to avoid this coating detachment problem is proposed. It is based on the use of a bioactive zirconia-calcium phosphate composite outer layer onto the zirconia bulk, where the zirconia bulk provides mechanical strength and the outer layer provides biological performance. In order to assess the potential of this new materials design, two types of bioactive zirconia outer composite layers (zirconia reinforced by 10 vol% of HAp and by 10 vol% of β-TCP) were produced by press and sinter process and the gradated samples were fully characterized concerning materials, mechanical resistance, fatigue resistance, and biological performance, as measured by different approaches. Results showed that the novel component materials design and the manufacturing process proposed for producing the bioactive zirconia samples with outer composite layers on zirconia bulk substrates are a promising solution for implants, with improved biological performance without substantially compromising their overall mechanical and fatigue properties.